Serum TRSUT Titer ≥1:16 Is a Predictor for Neurosyphilis Among HIV-Infected Patients With Concurrent Syphilis and No Neurological Symptoms. Issue 45 (November 2015) - Sun, Jian-Jun; Wang, Zhen-Yan; Shen, Jia-Yin; Shen, Yin-Zhong; Liu, Li; Wang, Jiang-Rong; Zhang, Ren-Fang; Lu, Hong-Zhou
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: Investigating the predictors for lumbar puncture to diagnose the asymptomatic neurosyphilis among HIV and syphilis co-infected patients in Shanghai, China. Respectively, screening the medical records from August 1, 2009 to June 30, 2015. Those HIV-infected patients with concurrent syphilis who had received lumbar puncture were selected and their clinical and demographic data were recorded. Participants comprised symptomatic and asymptomatic patients. The latter ones could be further divided into 3 groups: late syphilis, early syphilis with anti-syphilis treatment failure, and early syphilis with serum toludine red unheated serum test (TRUST) ≥1:32. Both syphilis stage and anti-syphilis treatment effect were defined by common criteria, and syphilis of unknown duration was considered as late syphilis. Asymptomatic neurosyphilis was defined as neurosyphilis without neurological symptoms such as headache, cognitive dysfunction, motor deficits, auditory or ophthalmic abnormalities, and stroke. Neurosyphilis was defined as reactive cerebrospinal fluid (CSF) TRUST and/or CSF white blood cell >20 cells/μL without other reasons. Mann–Whitney test and Fisher's exact test were used for analyzing the difference between neurosyphilis and non-neurosyphilis group. Logistic regression test was performed to analyze the risk factors for neurosyphilis. In total, 170 participants were collected, and the rate of neurosyphilis was 32.35%. Among all the 105 participants without neurological symptoms, 80 patients were with late syphilis and 25 were with early syphilis. Among the early syphilis patients, 23 had a TRUST ≥1:32 and the other 2 experienced an anti-syphilis treatment failure. The differences of clinical and demographic variables between neurosyphilis and non-neurosyphilis group were not statistically significant except the serum TRUST titer ( P  < 0.01). From HIV/syphilis co-infected patients with or without neurological symptom, those who had neurological symptoms, CD4 <350 per μL and serological TRUST titer ≥1:16 were 4.9-fold (95% confidence interval [CI]: 2.37–10.31), 4.3-fold (95% CI: 1.17–15.78), and 4.1-fold (95% CI: 1.58–10.76), respectively, more likely to be diagnosed with neurosyphilis. Asymptomatic patients whose serum TRUST titer ≥1:16 were 8.48-fold (95% CI: 1.08–66.63) more likely to have asymptomatic neurosyphilis. Among asymptomatic HIV-infected patients with late syphilis or early syphilis experienced an anti-syphilis treatment failure, those who have a serum TRUST titer ≥1:16 are suggested to perform lumbar puncture in order to avoid delayed diagnosis and the occurrence of severe sequelae of syphilis.